ТЕХНІЧНІ ЗАСОБИ ПОДАВЛЕННЯ РЕЗОНАНСНИХ ЯВИЩ В ЕЛЕКТРИЧНИХ МЕРЕЖАХ - В.В. Кучанський; О.В. Савицький (Праці Інституту електродинаміки Національної академії наук України, 2021)
The self-excitation phenomenon of generators connected to an unloaded power line is considered. Accordingly, the selected values of the conductivity of the controlled shunt reactors, following the control range (especially in the overload mode), avoid the occurrence of self-excitation of the generators. The physical analysis of the processes occurring at self-excitation of the synchronous generator is given, and the calculated models are developed. It is established that in the case of artificial support along the entire length of the voltage line at the nominal value using controlled compensating devices, the transmission will have properties characteristic of relatively short lines (up to 500 km) regardless of its geometric length. It is determined that the length of the line section at the ends of which the DC voltage is maintained is much less than 500 km. Therefore, less than the natural voltage along the section length will exceed the nominal value at the transmitted power, and the line will have excess reactive power. Consumption in intermediate compensation devices (compensation current must be inductive). Ref.8, fig. 4, tables 4.